An organelle-specific photoactivation and dual-isotope labeling strategy reveals phosphatidylethanolamine metabolic flux. Issue 7 (26th January 2023) - Simon, Clémence; Asaro, Antonino; Feng, Suihan; Riezman, Howard
Abstract : Organelle-targeting, photocaged, isotopically labeled analogs of phosphatidylethanolamine are developed to track how cells metabolize PE lipids that originate from the ER versus the mitochondria. Abstract : Phosphatidylethanolamine metabolism plays essential roles in eukaryotic cells but has not been completely investigated due to its complexity. This is because lipid species, unlike proteins or nucleic acids, cannot be easily manipulated at the single molecule level or controlled with subcellular resolution, two of the key factors toward understanding their functions. Here, we use the organelle-targeting photoactivation method to study PE metabolism in living cells with a high spatiotemporal resolution. Containing predefined PE structures, probes which can be selectively introduced into the ER or mitochondria were designed to compare their metabolic products according to their subcellular localization. We combined photo-uncaging with dual stable isotopic labeling to track PE metabolism in living cells by mass spectrometry analysis. Our results reveal that both mitochondria- and ER-released PE participate in phospholipid remodeling, and that PE methylation can be detected only under particular conditions. Thus, our method provides a framework to study phospholipid metabolism at subcellular resolution.